Hardware Protection through Obfuscation - Forte, Domenic; Bhunia, Swarup; Tehranipoor, Mark M. (Springer International Publishing : Imprint: Springer, 2017)
This book introduces readers to various threats faced during design and fabrication by today's integrated circuits (ICs) and systems. The authors discuss key issues, including illegal manufacturing of ICs or "IC Overproduction," insertion of malicious circuits, referred as "Hardware Trojans", which cause in-field chip/system malfunction, and reverse engineering and piracy of hardware intellectual property (IP). The authors provide a timely discussion of these threats, along with techniques for IC protection based on hardware obfuscation, which makes reverse-engineering an IC design infeasible for adversaries and untrusted parties with any reasonable amount of resources. This exhaustive study includes a review of the hardware obfuscation methods developed at each level of abstraction (RTL, gate, and layout) for conventional IC manufacturing, new forms of obfuscation for emerging integration strategies (split manufacturing, 2.5D ICs, and 3D ICs), and on-chip infrastructure needed forsecure exchange of obfuscation keys- arguably the most critical element of hardware obfuscation.